The Effect of Stress on the Menstrual Cycle in Adolescents - Ruji, Ruji; Syam, Hidayani; Erlin, Azie Utami; Hasanah, Fikratul; Wafiqah, Ulya (ALSYSTECH Journal of Education Technology, 2023)
The menstrual cycle is ideally regular every month, and this menstrual cycle normally occurs in the period of 21-35 days and usually lasts for 2-7 days. This menstrual cycle affects many things, including stress levels. This stress or stressor can occur, such as increased learning activity in adolescents which affects psychological factors and with this will also affect the menstrual cycle in adolescents. At the beginning of the period leading up to menstruation, women are more likely to get angry easily, cry easily for no reason or easily feel sad. This condition can sometimes make women feel uncomfortable and less enthusiastic about their activities. The purpose of writing this paper is to determine the relationship between stress levels and the menstrual cycle in adolescents.